2020
DOI: 10.1007/s41669-020-00195-x
|View full text |Cite
|
Sign up to set email alerts
|

DyeVert™ PLUS EZ System for Preventing Contrast-Induced Acute Kidney Injury in Patients Undergoing Diagnostic Coronary Angiography and/or Percutaneous Coronary Intervention: A UK-Based Cost–Utility Analysis

Abstract: Background Contrast-induced acute kidney injury (CI-AKI) is a complication commonly associated with invasive angiographic procedures and is considered the leading cause of hospital-acquired acute kidney injury. CI-AKI can lead to a prolonged hospital stay, with a substantial economic impact, and increased mortality. The DyeVert™ PLUS EZ system (FDA approved and CE marked) is a device that has been developed to divert a portion of the theoretical injected contrast media volume (CMV), reducing the overall volume… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…As a result, the number needed to treat for CI-AKI prevention is 20, preserving adequate image quality in 98% patients ( 141 ). Further information from a UK-based Cost-utility Analysis revealed that DyeVert™ results in cost savings as well as improved effectiveness over the course of a patient’s lifetime (−£435 and +0.028 QALYs) ( 142 ). The ongoing Renal Insufficiency Following Contrast Media Administration Trial IV (REMEDIAL IV) seeks to determine whether the DyeVert™ system is effective in lowering the rate of CI-AKI in patients with acute coronary syndrome undergoing urgent/immediate (within 2 h) invasive diagnostic or interventional cardiovascular procedures.…”
Section: Strategies To Prevent Contrast-induced Acute Kidney Injurymentioning
confidence: 99%
“…As a result, the number needed to treat for CI-AKI prevention is 20, preserving adequate image quality in 98% patients ( 141 ). Further information from a UK-based Cost-utility Analysis revealed that DyeVert™ results in cost savings as well as improved effectiveness over the course of a patient’s lifetime (−£435 and +0.028 QALYs) ( 142 ). The ongoing Renal Insufficiency Following Contrast Media Administration Trial IV (REMEDIAL IV) seeks to determine whether the DyeVert™ system is effective in lowering the rate of CI-AKI in patients with acute coronary syndrome undergoing urgent/immediate (within 2 h) invasive diagnostic or interventional cardiovascular procedures.…”
Section: Strategies To Prevent Contrast-induced Acute Kidney Injurymentioning
confidence: 99%
“…Currently, to our knowledge, there is no published economic evaluation in the Spanish context comparing Dyevert™ Power XT versus current standard practice in patients with CKD stages 3b‐4 undergoing PCI; however, a previous work evaluated the effectiveness of Dyevert™ in the UK setting 35 . The analysis here performed in Spain, used a similar approach, based on the same decision tree model and with slight differences on the Markov structure than the UK study.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible limitation is related to the use of data extracted from the literature of studies conducted in other countries. The utility values used in the present model derived from studies on different settings and countries 32–35 . No study specifically referring to a Spanish population with CKD was found by authors, so international values were applied, which were validated by the panel of experts to ensure that these values are representative of the Spanish population with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Briguori et al was the first report of a procedure-based CA-AKI prevention strategy resulting in significant CA-AKI reduction as well as a significantly shorter length of stay of about 2 days ( 30 ). Given the high cost of CA-AKI events ( 6 ), the overall economic value of the DyeVert System may be derived from CA-AKI avoidance based on recent hospital budget impact evaluations ( 32 , 40 , 41 ) and a modeling study ( 44 ).…”
Section: Discussionmentioning
confidence: 99%